Digitization of Tafsir and its Challenge to the Authority of Interpretation: A Review of Ulumul Qur'an - Abdul Rouf (Jurnal QOSIM : Jurnal Pendidikan, Sosial & Humaniora, 2025)
The development of digital technology has brought significant changes in the way Muslims access and understand Qur'anic interpretation. This study aims to analyze the impact of digitalization on the authority of Qur'anic interpretation from the perspective of Ulumul Qur'an. The method used is a literature study by analyzing twenty relevant academic literatures. The results show that digitization increases access to sources of interpretation, but also causes a shift in authority from authoritative scholars to popular digital figures without sufficient scientific basis. Much of the tafsir content does not utilize a comprehensive Ulumul Qur'an approach, making it prone to biased and distorted interpretations. Ulumul Qur'an has an important role as a scientific filter in assessing the validity of digital interpretations and needs to be revitalized in the curriculum and digital da'wah platforms. This study concludes that the integration of Ulumul Qur'an in the digitalization of tafsir is a strategic step to maintain the authority, validity, and depth of understanding of the Qur'an